Conceptual Framework of Performance Management for Northern Iraq Construction Industry - Pirot, Bilal Mohammed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Due to increasing competition between construction companies and changing demands on the type and quality of construction projects in the last two decades, the importance of performance management has been significantly elevated. Therefore, in the recent years a need for a comprehensive system of performance management has been identified for construction organizations. Performance management is a proactive closed loop control system which provides effective strategies for the organizational procedures, tasks, and activities and performs feedback on the whole processes of the system. Since 2003, construction industry in Northern Iraq (NIQ) has been significantly developed and business links of the region with the other countries has been substantially progressed. In addition, due to the stability which exists in the region compared with the other parts of Iraq, the region has been focused by international construction companies. Despite of that, the involvement of foreign companies in the region has been facilitated by Kurdistan Regional Government (KRG) as a strategy to gain international expertise and foreign technical competency. As a result, a competitive environment for international and local companies has been created in the region that made construction companies make a great effort for improving their performance within the industry. The main objectives of this study are to analyze the existing performance management system (PMS) in NIQ construction industry on the base of recognizing the most appropriate performance measures for construction companies working in the region and proposing a framework by using these measures. For the purpose of forming a suitable framework for NIQ construction industry, two different techniques Balanced Scorecard (BSC) and European Foundation for Quality Management (EFQM) have been adapted with the addition of a number of perspectives regarding to the business environment of construction industry in NIQ. Furthermore, a questionnaire survey has been performed among the construction organizations working in the region to know the importance level of the framework variables/perspectives. The questionnaire has been sent through e-mail, transmitted in social networks, and filled in face-to-face meetings among NIQ construction companies. As a result, a framework of performance management has been introduced that can be used as a management control system for managing and evaluating performance of NIQ construction organizations. Since in developing the framework two different frameworks have been used and some other perspectives have been added based on experience, the study can be considered as a significant contribution to the field. Furthermore, the framework can be further investigated to be used as a control system in different times and countries. Keywords: Performance management, Performance measurement, Management control system, Strategic management, Northern Iraq Construction industry.

ÖZ: İnşaat şirketleri arasında artan rekabet ve son yirmi yılda inşaat projelerinin türü ve kalitesinde değişen talepler, nedeniyle performans yönetiminin önemi önemli ölçüde yükselmiş oldu. Bu nedenle son yıllarda inşaat kuruluşları için kapsamlı bir performans yönetim sistemine olan ihtiyaç tespit edilmiştir. Performans yönetim sistemi, örgütsel prosedürler, görevler ve etkinliklere katılım için etkili stratejiler sağlayan proaktif kapalı çevrim bir kontrol sistemidir ve sistemin tüm süreçlerine performans geri bildirimi gerçekleştirir. 2003 yılından bu yana, Kuzey Irak'ta (KI) inşaat sektörü önemli ölçüde geliştirilmiştir ve diğer ülkelerle bölgenin iş bağlantıları önemli ölçüde ilerlemiştir. Buna ek olarak, Irak'ın diğer bölgeleri ile karşılaştırıldığında bölgede var olan istikrar nedeniyle, bölge uluslararası inşaat şirketleri tarafından odanlanmıştır. Buna rağmen, bölgedeki yabancı şirketlerin katılımı, uluslararası uzmanlık ve yabancı teknik yeterliklerini kazandırmak için bir strateji olarak Kürdistan Bölgesel Hükümeti (KBH) tarafından kolaylaştırılmıştır. Sonuç olarak, bölgede büyük bir çaba ile inşaat şirketlerinin sektörde kendi performanslarını artırmalarını sağlayayan uluslararası ve yerel şirketler için rekabet ortamı oluşturulmuştur. Bu çalışmanın temel amacı, bölgede faaliyet gösteren inşaat firmaları için en uygun performans ölçütlerini belirlemeye ve bu ölçütleri kullanarak bir çerçeve önermeye yönelik KI inşaat sektöründeki mevcut Performans Yönetim Sistemini (PMS) analiz etmektir. KI inşaat sektörü için uygun bir çerçeve oluşturulması amacıyla, iki farklı teknik olan Dengeli Karne (DK) ve Avrupa Kalite Yönetimi Vakfı (AKYV), KI inşaat sektöründeki iş ortamına ilişkin bir dizi bakış açılarının eklenmesi ile adapte edilmiştir. Ayrıca, çerçeve değişkenler / bakış açıları önem seviyesini öğrenmek için bölgede faaliyet gösteren inşaat frmaları arasında bir anket çalışması yapılmıştır. Anketler sosyal ağlarda iletilen, e-posta yoluyla gönderilen ve KI inşaat şirketleri arasında yüz-yüze yapılan mülakatlarla dolduruluştur. Sonuç olarak, KI inşaat firmalarının performansını yönetmek ve değerlendirmeye yönelik bir yönetim kontrol sistemi olarak kullanılabilecek bir çerçeve performans yönetimi sunulmuştur. Bu çerçevenin geliştirilmesi ile iki farklı çerçeve deneyimi gerçekleştirilmiş ve diğer bazı perspektiflerin de eklenerek, çalışılan alanında önemli bir katkı sağlanmıştır. Bundan başka, çerçeve daha farklı zamanlarda ve ülkelerde, bir kontrol sistemi olarak kullanılmak üzere araştırılabilir. Anahtar kelimeler: Performans yönetimi, Performans ölçümü, Yönetim control sistemi, Strateji yönetimi, Kuzey Irak İnşaat Sektörü.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Assoc. Prof. Dr. İbrahim Yitmen.
Keywords: Civil Engineering; Construction Industry - Iraq, North; Performance management; Performance measurement; Management control system; Strategic management; Northern Iraq Construction industry